Evaluasi Kapasitas Tampungan Saluran Drainase Menggunakan Storm Water Management Model - Sulwan Permana; Azqia Fhairiza Rusmana (Institut Teknologi Garut, 2026)
Population growth and land use change in Sukagalih Village, Garut Regency, have increased surface runoff volume, triggering flooding at several points in the drainage system. This study aims to evaluate the drainage system's storage capacity using Storm Water Management Model (SWMM) modeling and provide technical recommendations for improving its performance. The method used is quantitative descriptive with primary data in the form of survey results on the physical condition and dimensions of the channels, as well as secondary data including rainfall, topography, and land use. Hydrological analysis was carried out through the calculation of planned rainfall using a normal distribution, rainfall intensity using the Mononobe method, and rainfall distribution using the Alternating Block Method. The SWMM simulation results showed that six junctions (JN27, JN29, JN30, JN32, JN36, and JN51) experienced overflow during peak rainfall due to sedimentation, wild vegetation, and channel dimension limitations. The technical evaluation recommended routine cleaning, sediment removal, and channel dimension improvement at vulnerable points. The application of these recommendations in a re-simulation showed an improvement in flow capacity and a reduction in overflow, thereby increasing the effectiveness of the drainage system in controlling flooding in Sukagalih Village. The results of this study can be used as a reference in planning a sustainable urban drainage system.